De cráneos, debates y flujos de información. Los inicios de la Antropología Física en la Argentina y L´École d´Anthropologie de París - Quijada, Mónica (Revista Complutense de Historia de América, 2010)
This article analyses some aspects of the work of the argentine scientist Francisco Pascasio Moreno –founder of the La Plata Museum of Natural Sciences-, in particular his connexions with the French physical anthropologists gathered around Paul Broca in the institutions he had founded in Paris: the Société d’Anthropologie and the École d’Anthropologie. The aim of this work is to shed light on the scientific exchanges between Latin American and European intellectuals in the 19th Century, pointing out the relevance and dynamism of the information flows and the recognition achieved by some Latin American scientists in the French anthropological institutions and media, in the framework of one of the most recent and state-of-the-art controversies of the time: the debates on the origin of man.
Keywords: Science; Europe and America; Scientifical Exchanges; Scientifical Institutions; Origin of Man; Explorations; Physical Anthropology; Argentina; 19th Century